Happiness and Physical Discomfort as Determinants of Quality of Life Among Nursing Home Residents: A Cross-Sectional Study - Masithoh, Anny Rosiana; Murdhiono, Wahyu Rochdiat; Nordin, Rusli Bin Nordin; Rahmawati, Ashri MaulidaRahmawati (Chakra Brahmanda Lentera Institute, 2026)
Background: QoL assessment is essential in delivering person-centered care for institutionalized older adults. However, evidence on the combined influence of happiness and physical discomfort on their QoL remains limited. This study aimed to examine the associations between happiness, physical discomfort, and QoL among nursing home residents. Methods: This cross-sectional study followed the STROBE guideline and was conducted at Nursing Home A in Jepara Regency. Of the 81 elderly residents, 68 participants were selected using Slovin’s formula and recruited through purposive sampling. Inclusion criteria were age ≥60 years, permanent residence in the nursing home, willingness to participate, and ability to communicate effectively. The independent variables were happiness and physical discomfort, while QoL was the dependent variable. The questionnaires were administered through face-to-face interviews to ensure comprehension. QoL was assessed using the SF-36, happiness using the Oxford Happiness Questionnaire (OHQ), and physical discomfort using the Visual Analogue Scale (VAS). Associations between variables were analyzed using Spearman’s rank correlation test. Results: The majority of elderly participants reported experiencing severe physical discomfort (33.8%) and demonstrated poor QoL (58.8%). A significant association was identified between physical discomfort and QoL (Spearman’s ρ = −0.37, 95% CI −0.56 to −0.14, p = 0.003). In addition, happiness was significantly correlated with QoL (Spearman’s ρ = 0.35, 95% CI 0.12 to 0.54, p = 0.004), with most participants who exhibited low happiness scores also reporting poor QoL. Conclusion: The findings underscore the importance of integrated nursing strategies that address both physical discomfort management and emotional well-being to improve elderly QoL. Routine assessment of discomfort and happiness should be incorporated into daily nursing care and institutional policies within nursing homes.